Biostimulation for the Enhanced Degradation of Herbicides in Soil - Ramdas Gopinath Kanissery; Gerald K. Sims (Applied and Environmental Soil Science)
Cleanup of herbicide-contaminated soils has been a dire environmental concern since the advent of industrial era. Although microorganisms are excellent degraders of herbicide compounds in the soil, some reparation may need to be brought about, in order to stimulate them to degrade the herbicide at a faster rate in a confined time frame. “Biostimulation” through the appropriate utilization of organic amendments and nutrients can accelerate the degradation of herbicides in the soil. However, effective use of biostimulants requires thorough comprehension of the global redox cycle during the microbial degradation of the herbicide molecules in the soil. In this paper, we present the prospects of using biostimulation as a powerful remediation strategy for the rapid cleanup of herbicide-polluted soils.